(untitled) (Journal of the College of Basic Education, 2022)
Iraqi students at preparatory schools encounter difficulties when speaking English as a foreign language .So, this study aims to investigate Iraqi sixth-year preparatory school students’difficulties in the speaking skill according to the gender and specialty variables . Accordingly, a survey is conducted in nine preparatory schools of AL-Risafa 1/ General Directorate of Education :(418) students from the sixth-year scientific branch ( 210 males & 208 females) and (342) students from the literary branch (170 males & 172 females),in Baghdad, during the first term of the academic year (2015-2016).A suitable questionnaire of 10 items is designed and exposed to a jury of specialists in ELT. The results indicate that the subjects of the study , i.e. preparatory school students are poor in speaking the foreign language .This is due to the lack of teaching methods, pronunciation ,cultural knowledge, motivation ,self confidence, exposure to English spoken in class ,vocabulary, and grammar. Then, conclusions ,recommendations, and suggestions are put forward.